Study on the Retention and Distributions of the Copper-Based Preservative in Standing Tree Chinese Fir (Cunninghamia lanceolata) - Youhua Fan; Yong Wang; Ninghua Yu; Layun Deng; Zejun Chen (Advances in Materials Science and Engineering)
In spite of some studies about the wood permeability and its improving measures, some progress has been made to study the diffusion and transmission of preservative solutions in standing trees. In the present study, copper- (Cu-) based preservative with other reagents is injected into the standing tree Chinese fir using sap-flow method. The chemical compositions of the retreated woods are analyzed with Fourier transform infrared spectroscopy (FTIR) and X-ray photoelectron spectroscopy (XPS). The samples from different height positions are analyzed with scanning electron microscope (SEM) and atomic absorption spectroscopy (AAS) to obtain microstructures and preservative retention, respectively. The results indicate that the preservative solutions with lower concentrations are more conducive to diffusion and transmission in the wood. Moreover, the preservative retention at different height position has a greater concentration gradient for composite preservative solutions than those of the single preservative solutions. Solidified preservative particles are observed in xylem rays with SEM. The results of the present study provide some useful information for the functional design of the target wood products.